Feasibility Randomised Trial Comparing Two Forms of Mental Health Supported Accommodation (Supported Housing and Floating Outreach); a Component of the QuEST (Quality and Effectiveness of Supported Tenancies) Study - Killaspy, Helen; Priebe, Stefan; McPherson, Peter; Zenasni, Zohra; McCrone, Paul; Dowling, Sarah; Harrison, Isobel; Krotofil, Joanna; Dalton-Locke, Christian; McGranahan, Rose; Arbuthnott, Maurice; Curtis, Sarah; et al. (Frontiers in Psychiatry, 2019)
Abstract Background: Mental health supported accommodation services are implemented across England, usually organised into a ‘step-down’ care pathway that requires the individual to repeatedly move as they gain skills and confidence for more independent living. There have been no trials comparing the effectiveness of different types of supported accommodation but two widely used models (supported housing and floating outreach) have been found to provide similar support. We aimed to assess the feasibility of conducting a large scale trial comparing these two models. Methods: Individually randomised, parallel group feasibility trial in three regions of England (North London, East London, Cheltenham and Gloucestershire). We aimed to recruit 60 participants in 15 months, referred to supported accommodation, randomly allocated on an equal basis to receive either a local supported housing or floating outreach service. We assessed: referrals to the trial; participants recruited; attrition; time from recruitment to moving into either type of supported accommodation; feasibility of masking. We conducted a process evaluation to interrogate our results further. Results: We screened 1,432 potential participants, of whom 17 consented to participate, with 8 agreeing to randomisation (of whom 1 was lost to attrition) and 9 participating in naturalistic follow-up. Our process evaluation indicated that the main obstacle to recruitment was staff and service user preferences for certain types of supported accommodation or for specific services. Staff also felt that randomisation compromised their professional judgement. Conclusions: Our results do not support investment in a large scale trial in England at this time. Trial registration: UK CRN Portfolio database (Trial ID: ISRCTN19689576). Trial funding: National Institute of Health Research (RP-PG-0707-10093).